PENYELESAIAN KONFLIK TRANSGENDER OLEH KOMUNITAS STARAMUDA JOMBANG: PERSPEKTIF KOMUNIKASI LINTAS BUDAYA - Maghfiroh, Rifqotul; Sumarah, Noorshanti; Soenarjanto, Bagus (representamen, 2015)
The third gender identitieâ€™s phenomenon called "transgender" causing the pros and contoversial,especially the Jombangâ€™s societies having a negative stigma about the existence of transgender so itâ€™sarising a discrimination conflict. Based on the observations of researcher, wanted to know the extent ofconflict resolution for the transgender in the Jombangâ€™s societies that has labeled â€œKota Santriâ€. HowStaramuda Communitieâ€™s roles as a communicator to merge conflict negative stigma of transgender thatlives in Jombang societies having a dominant of Islamic culture, by using communicative approach. Thisresearch uses a qualitative research to describe and analyze the phenomena, incident, social activities,attitudes, perceptions and ideas between the transgender being protected by Staramuda and Jombangsociety. By using the method of â€œindepth interviewâ€ with the informants of Staramuda Community andthe transgender, indicate results some of the causes of conflict related to cultural communication. Firstly,the existence of transgender considered as a violation of culture. The second, the diversity for minoritiesgender isnâ€™t complete yet, especially for the transgender. Reviewed from DeVitoâ€™s about culturalcommunication, Staramuda community have their own viewpoint about the existence of transgender thatthey are also part of society of â€œKota Santriâ€ Jombang, by using an attitude of open-mindness, positiveattitude could change a negative stigma, social support, emphaty, which raised the equality in the society.Keywords : cultural communication, cultural conflict, transgender